UV-B Radiation Tolerance and Temperature-Dependent Activity Within the Entomopathogenic Fungal Genus Metarhizium in Brazil - Couceiro, Joel da Cruz; Fatoretto, Maíra Blumer; Demétrio, Clarice Garcia Borges; Meyling, Nicolai Vitt; Delalibera, Ítalo (Frontiers in Fungal Biology, 2021)
Metarhizium comprises a phylogenetically diverse genus of entomopathogenic fungi. In Brazil, Metarhizium anisopliae s.str. subclade Mani 2 is predominantly isolated from insects, while M. robertsii and M. brunneum mostly occur in the soil environment. Solar radiation and high temperatures are important abiotic factors that can be detrimental to fungal propagules. We hypothesized that among 12 Brazilian isolates of Metarhizium spp., M. anisopliae Mani 2 (n=6), being adapted to abiotic conditions of the phylloplane, is more tolerant to UV light and high temperatures than M. robertsii (n=3) and M. brunneum (n=3). Inoculum of each isolate was exposed to UV-B for up to 8 h and viability evaluated 48 h later. After 8 h under UV-B, most of the isolates had germination rates below 5%. Discs of mycelia were incubated at different temperatures, and diameter of colonies were recorded for 12 days. Mycelia of M. robertsii isolates grew faster at 33 °C, while M. anisopliae and M. brunneum grew most at 25 °C. Dry conidia were incubated at 20, 25 or 40 °C for 12 days, and then viabilities were examined. At 40 °C, conidia of five M. anisopliae isolates were the most tolerant. In the three experiments, considerable intra- and inter-specific variability was detected. The results indicate that conclusions about tolerance to these abiotic factors should be made only at the isolate level.